Indoor Air Pollution in Cold Climates : The Cases of Mongolia and China - Baris, Enis; Rivera, Salvador; Boehmova, Zuzana; Constant, Samantha (World Bank, Washington, DC, 2014)
This note provides a snapshot of indoor air pollution interventions in two cold climate environments. It illustrates the different methodologies used for each of the cases and presents a comparative analysis of results and lessons learned.